A polishing pad and its preparation method and use
By using polishing pads prepared with materials such as modified polyethersulfone resin and polyurethane resin, the problem of poor durability of silicon carbide substrate polishing pads in the prior art during the CMP process is solved, and higher oxidation resistance and service life are achieved, and polishing efficiency and substrate surface quality are improved.
Patent Information
- Application Number
- CN202411062718.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The polishing pads of existing silicon carbide substrates are prone to fall off due to strong oxidant corrosion during high-pressure and high-speed CMP, resulting in a decrease in polishing removal rate and poor product durability.
Modified polyethersulfone resin and polyurethane resin are used as resin materials, combined with pore-forming agents, and polishing pads are prepared through impregnation and solidification processes to improve their oxidation resistance and toughness.
The oxidation resistance and service life of the polishing pad is significantly improved, the polishing rate and substrate surface quality are improved, and the breathability and toughness of the polishing pad are enhanced.
Smart Images

Figure CN119036303B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of CMP material preparation in silicon carbide substrate processing, and in particular to a polishing pad and a preparation method and application thereof. Background Art
[0002] Silicon carbide (SiC), as the third generation wide bandgap semiconductor material, has the characteristics of large bandgap width, high thermal conductivity, high critical breakdown field strength, and high electron saturation drift rate. It can effectively break through the physical limits of traditional silicon-based semiconductor devices and their materials, and develop a new generation of semiconductor devices that are more adaptable to high pressure, high temperature, high power, high frequency and other conditions. SiC is the third hardest material in the world. It not only has the characteristics of high hardness, but also high brittleness and low fracture toughness, which makes it easy to cause brittle fracture of the material during grinding, leaving a surface crushing layer on the surface of the material, and causing more serious surface and subsurface damage, affecting the processing accuracy.
[0003] The high processing difficulty of silicon carbide in the cutting, grinding and polishing stages is mainly reflected in: (1) high hardness, with a Mohs hardness distribution of 9.2 to 9.6; (2) high chemical stability, almost no reaction with any strong acid or strong base; (3) processing equipment is not yet mature. The substrate processing procedures are very cumbersome, and the inefficient and complex processing technology leads to serious shortage of production capacity and output. In order to achieve high removal and flattening of silicon carbide substrates, the current double-sided CMP process of silicon carbide substrates uses a non-woven polishing pad with a potassium permanganate system polishing liquid. However, potassium permanganate is a strong oxidant and will corrode the polyurethane coating of the non-woven polishing pad. During the high-pressure and high-speed CMP process, the polyurethane impregnated on the non-woven fabric is easy to fall off, the non-woven polishing pad becomes fuzzy, the fiber falls off and blocks the filter, and the polishing removal rate decreases.
[0004] Invention patent CN200880003811 adopts the method of bundled fibers. By bundling the ultrafine single fibers constituting the fiber bundle and making them exist in the state of a coarse fiber, a polishing pad with high rigidity can be obtained. Patent CN108349062 weaves the raw material fibers in warp and weft, modifies the raw materials, enhances the toughness and strength of the non-woven fabric, and thus improves the hardness of the final product. Patent CN201480007963 adopts the method of secondary impregnation, pre-impregnates a softer polyurethane resin, and then impregnates another resin after solidification, which can be cured and cross-linked, and the performance of the final product can also be improved. Invention patent JP2012101333A discloses a preparation process for a polishing pad, which adopts a wet coating process to apply a layer of resin on a plastic film, improves the mechanical strength of the final product by mixing two resins of different hardness, and improves the pore structure by wet coagulation. However, after the product prepared by this method is oxidized, once the molecular bonds of the resin film are broken, the resin film on the surface of the product is easy to crack, thereby affecting the polishing effect.
[0005] The above method has complicated procedures and operations, and only improves the mechanical properties of the polishing pad, which can improve the polishing efficiency to a certain extent. However, due to the influence of strong oxidants in the polishing liquid, the polishing pad still has the defect of being not durable. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a polishing pad and a preparation method and use thereof, so as to solve the problems in the prior art.
[0007] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0008] The invention discloses a polishing pad, comprising a base material, wherein the base material is impregnated with a resin material, wherein raw material components of the resin material include resin and a pore-forming agent; and the resin includes modified polyethersulfone resin and polyurethane resin.
[0009] Preferably, the polyurethane resin accounts for 10% to 30% of the resin mass, such as 10% to 20%, 20% to 30%. The more the polyurethane resin is used, the better the toughness of the polishing pad and the worse the oxidation resistance.
[0010] Preferably, the modified polyethersulfone resin accounts for 70% to 90% of the resin mass, such as 70% to 80% or 80% to 90%.
[0011] Preferably, the pore-forming agent accounts for 0.3-1% of the mass of the resin. For example, it can be 0.3-0.5%, 0.5-0.8%, 0.8-1.0%. The more the pore-forming agent is used, the better the air permeability, the worse the oxidation resistance, and the better the toughness of the polishing pad. The more the resin is used, the worse the air permeability, the better the oxidation resistance, and the worse the toughness of the polishing pad.
[0012] Preferably, the pore former is selected from polyacrylic acid and / or polyvinyl alcohol.
[0013] More preferably, the weight average molecular weight of the polyacrylic acid is 20,000 to 60,000, such as 20,000 to 30,000, 30,000 to 40,000, 40,000 to 50,000, or 50,000 to 60,000.
[0014] More preferably, the weight average molecular weight of the polyvinyl alcohol is 50,000 to 100,000, such as 50,000 to 75,000, 75,000 to 80,000, 80,000 to 90,000, or 100,000 to 100,000.
[0015] Preferably, the modified polyethersulfone resin is obtained by a grafting reaction of acrylic acid and polyethersulfone.
[0016] More preferably, the mass ratio of the polyethersulfone to the acrylic acid is 10:(0.1-1), such as 10:(0.1-0.3), 10:(0.3-0.5), 10:(0.5-0.7), 10:(0.7-1).
[0017] Preferably, the weight average molecular weight of the polyethersulfone resin is 10000-70000, such as 10000-20000, 20000-30000, 30000-40000, 40000-50000, 50000-60000, 60000-70000, more preferably 30000-50000.
[0018] Preferably, the 100% modulus of the polyurethane resin is 1-15 MPa, such as 1-5 MPa, 5-7 MPa, 7-10 MPa, or 10-15 MPa.
[0019] Preferably, the raw material component further includes a first solvent, and the first solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0020] Preferably, the base material is selected from fabric, non-woven fabric or woven fabric. The resin material is filled between the fibers of the base material. When oxidized, even if the molecular bonds of the resin material are broken, the polishing pad will not crack, thereby affecting the polishing effect.
[0021] More preferably, the fiber raw material of the non-woven fabric includes one or more of polypropylene, polyester, nylon, viscose, acrylic, polyethylene, chloroprene, polyester and polyamide fibers.
[0022] Preferably, the fiber raw material of the base material has a fiber fineness of 2.6 to 3.0 deniers.
[0023] Preferably, the polishing pad comprises one or more of the following features:
[0024] a) Density: 0.4~0.5g / cm 3 ; b) Shore A hardness is 80-91HA; c) compression rate is 2.0-4.0%; d) compression elasticity is 60-75%; e) air permeability is not less than 100m 2 / S; f) After being immersed in an alkaline potassium permanganate solution having a concentration of 4.5-5.5% and a pH of 8.5-9.5, the surface was abraded with an H-18 ceramic grinding wheel with a load of 1-2 kg and rotated 500-600 times at a speed of 60-75 rpm, and the wear amount was not higher than 100 mg.
[0025] For example, the air permeability of the polishing pad can be 102m 2 / S, 110m 2 / S、185m 2 / S、191m 2 / S, 233m 2 / S.
[0026] For example, the wear amount of the polishing pad can be 41 mg, 57 mg, 61 mg, and 67 mg.
[0027] The present invention also discloses a method for preparing the polishing pad as described above, comprising the following steps:
[0028] 1) mixing the raw material components to form a homogeneous impregnation solution;
[0029] 2) The base material is immersed in the immersion liquid, and then placed in a coagulation liquid for coagulation to obtain the polishing pad.
[0030] Preferably, in the impregnation solution, the content of the modified polyethersulfone resin is 15-25wt%, such as 15-16wt%, 16-18.3wt%, 18.3-19.2wt%, 19.2-20wt%, 20-23.5wt%, 23.5-25wt%.
[0031] Preferably, in the impregnation liquid, the content of the polyurethane resin is 2-10wt%, such as 2-2.6wt%, 2.6-4wt%, 4-4.8wt%, 4.8-7.8wt%, or 7.8-10wt%.
[0032] Preferably, in the impregnation solution, the content of the pore-forming agent is 0.1-0.2 wt %.
[0033] Preferably, the modified polyethersulfone resin is subjected to drying pretreatment before use, and the drying temperature is 110-130°C.
[0034] Preferably, the base material is subjected to a drying pretreatment before the impregnation treatment, and the drying temperature is 90-120°C.
[0035] Preferably, before the impregnation treatment, the impregnation liquid is subjected to a vacuum degassing treatment.
[0036] Preferably, the impregnation is followed by a rolling process.
[0037] More preferably, the rotation speed of the rubber roller is 1 to 5 r / min, and the roller pressure is 0.1 to 1.0 MPa.
[0038] Preferably, the coagulation liquid is an aqueous solution of N,N-dimethylformamide.
[0039] More preferably, in the coagulation liquid, the content of N,N-dimethylformamide is 17-22 wt %, such as 15-20 wt %, 20-25 wt %.
[0040] Preferably, after the solidification treatment, one or more treatments selected from washing, drying, grinding and grooving are performed.
[0041] More preferably, the drying temperature is 120-130°C, and the drying time is 2-3 hours. For example, the drying temperature may be 100-110°C, 110-120°C, 120-130°C, 130-140°C, or 140-150°C.
[0042] More preferably, the polishing is performed by polishing both sides of the polishing pad with sandpaper having a mesh number of 170 to 200.
[0043] Preferably, the thickness of the base material is 1.8-2.2 mm, and the weight is 270-330 g / cm 2 ..
[0044] The invention also discloses the use of the polishing pad as described above as a polishing pad for polishing a silicon carbide substrate in chemical mechanical polishing.
[0045] The present invention discloses a polishing pad and a preparation method and use thereof, which have the following beneficial effects:
[0046] The present application adopts modified polyethersulfone resin as the polishing pad resin, which greatly improves the oxidation resistance of the polishing pad, thereby increasing the service life of the polishing pad for polishing SiC substrates and improving durability; a certain amount of low modulus polyurethane resin is added to the modified polyethersulfone resin, which improves the toughness of the polishing pad while ensuring oxidation resistance, so that it has a certain rebound ability; and a small amount of pore-forming agent is added to increase the porosity of the polishing pad. The components are matched in a specific ratio so that the prepared polishing pad has good oxidation resistance, air permeability, and toughness at the same time. When used for polishing SiC substrates, the polishing rate and substrate surface quality are both good, while also increasing the service life of the polishing pad. The preparation method is simple, only one step of impregnation and solidification is required, no additional processes are required, the production efficiency is high, the cost is low, and it is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The test results of the polishing rates of the polishing pads prepared in Example 3 of the present invention and Comparative Examples 1 to 3 and 8 and the commercially available polishing pad suba800 are shown.
[0048] Figure 2 The test results of the number of scratches on the polishing pads prepared in Example 3 of the present invention and Comparative Examples 1 to 3 and 8 and the commercially available polishing pad suba800 are shown.
[0049] Figure 3 The test results of the polishing rates of the polishing pads prepared in Example 1 of the present invention and Comparative Examples 4-5 are shown.
[0050] Figure 4 The test results of the scratch quantity of the polishing pads prepared in Example 1 of the present invention and Comparative Examples 4-5 are shown.
[0051] Figure 5 The test results of the polishing rates of the polishing pads prepared in Example 3 of the present invention and Comparative Examples 6-7 are shown.
[0052] Figure 6 The test results of the scratch quantity of the polishing pads prepared in Example 3 of the present invention and Comparative Examples 6-7 are shown.
[0053] Figure 7 The figure shows the surface effect of the polishing pad prepared in Example 3 of the present invention after the oxidation resistance test.
[0054] Figure 8 The figure shows the surface effect of the polishing pad prepared in Comparative Example 1 of the present invention after the oxidation resistance test.
[0055] Fig. 9 The figure shows the surface effect of the polishing pad prepared in Comparative Example 7 of the present invention after the oxidation resistance test.
[0056] Fig.10 The surface effect diagram of the polishing pad prepared in Example 3 of the present invention after a 20-hour polishing rate test is shown.
[0057] Fig.11 This is a surface effect diagram of the polishing pad prepared in Comparative Example 1 of the present invention after a 20-hour polishing rate test.
[0058] Fig.12 This is a surface effect diagram of the polishing pad prepared in Comparative Example 7 of the present invention after a 20-hour polishing rate test. DETAILED DESCRIPTION
[0059] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0060] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0061] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0062] The modified polyethersulfone resin of the present invention is prepared by the following method:
[0063] The pretreated polyethersulfone is dissolved in the second solvent, and then the acrylic acid monomer is added, and the mixture is stirred at 60-80°C to obtain a homogeneous solution; in an oxygen-free atmosphere, the homogeneous solution is placed under a radiation source for radiation reaction, the radiation reaction temperature is 10-30°C, the radiation dose rate is 0.5-5kGy / h, and the total radiation dose is 5-30kGy. After the reaction is completed, the homogeneous solution is reversely precipitated in an aqueous solution, washed repeatedly for multiple times, soaked in water for 20-30 hours, and vacuum dried.
[0064] Specifically, the pretreatment method of the polyethersulfone resin is: washing the polyethersulfone resin in water and soaking it for more than one week, changing the water several times during the period, and then drying it to constant weight under vacuum at 70-80°C.
[0065] Specifically, the second solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
[0066] Specifically, the mass ratio of the polyethersulfone to the acrylic acid monomer is 10:(0.1-1).
[0067] Specifically, the amount of the polyethersulfone in the homogeneous solution is 5 to 20 wt %.
[0068] Specifically, the radiation source is generally a gamma ray radiation source, preferably 60 C O .
[0069] Specifically, the oxygen-free atmosphere can be provided by exhausting oxygen by introducing nitrogen and / or an inert gas.
[0070] The specific implementation method of the present invention further provides a specific method for preparing a polishing pad, and the preparation steps are as follows:
[0071] (1) Preparation of impregnation solution:
[0072] A certain amount of modified polyethersulfone resin powder is weighed, dried in an oven at 110-130° C. for 12-24 hours to remove any residual moisture, and DMF is added and stirred for 30-45 minutes using a high-speed shear disperser to fully dissolve the mixture to form a solution A with a solid content of 20-35%wt, wherein the weight average molecular weight of the modified polyethersulfone powder is 10,000-70,000.
[0073] Weigh a certain amount of polyurethane resin solution, add DMF, and stir and disperse with a mixer at high speed for 30 to 45 minutes to form solution B, with a solid content controlled at 20-35%wt. The 100% modulus of the polyurethane resin is 1-15Mpa.
[0074] A certain amount of pore-forming agent is weighed and added to the first solvent DMF, and dispersed by high-speed stirring for 30 to 45 minutes to obtain solution C with a solid content of 1 to 5% wt. The pore-forming agent is selected from polyacrylic acid and / or polyvinyl alcohol.
[0075] The three solutions A, B and C are mixed in a mass ratio of 60-80:10-30:10-30, stirred and degassed to form an impregnation solution, which is then allowed to stand for use.
[0076] (2) Wet forming of polishing pad:
[0077] The non-woven fabric base is pre-treated in an oven at 100-150°C for 1-2 hours to remove moisture, and then the non-woven fabric base is immersed in the impregnation liquid, and the excess floating material on the surface is squeezed out by a pressure roller. The non-woven fabric base is immersed in the coagulation liquid to coagulate the resin on the non-woven fabric fibers. After washing with water, it is dried at 120-130°C for 2-3 hours to obtain a semi-finished polishing pad.
[0078] The coagulation liquid is an aqueous solution of N,N-dimethylformamide with a concentration of 15-25wt%. The non-woven fabric is made of short fibers by needle punching process, and the fiber raw material is selected from one of polypropylene, polyester, nylon, viscose, acrylic, polyethylene, chloroprene, polyester and polyamide. The fiber fineness of the fiber raw material is 2.6-3.0 denier. The thickness of the non-woven fabric is 1.8-2.2mm, and the gram weight is 270-330g / cm 2 ..
[0079] (3) Polishing pad processing
[0080] Grind both sides of the semi-finished polishing pad with 170-200 grit sandpaper to control the thickness of the product to 1-1.5 mm. Then apply double-sided tape on one side and make grooves on the other side. After completion, the polishing pad is finished.
[0081] The following are more specific examples. The reagents and instruments used in the following examples are all commonly used reagents and can be purchased from the market, as follows:
[0082] The polyurethane resin solution was purchased from Asahikawa Chemical with a concentration of 35 wt%. It was prepared from polyester polyol and MDI (diphenylmethane diisocyanate). The first solvent was DMF.
[0083] In the following examples, the weight average molecular weight of polyacrylic acid is 40,000, and the weight average molecular weight of polyvinyl alcohol is 75,000.
[0084] Example 1
[0085] This embodiment provides a specific method for preparing a polishing pad, and the preparation steps are as follows:
[0086] (1) Preparation of modified polyethersulfone resin: 10 g of pretreated polyethersulfone powder was weighed and dissolved in 86 g of DMF solvent. 1 g of acrylic acid monomer was added and stirred at 60 °C for 24 h to obtain a homogeneous solution. N 2 After 15 min, the homogeneous solution was placed 60 C O The irradiation reaction was carried out at 20°C under a source, the irradiation dose rate was 1 kGy / h, and the absorbed dose was 17 kGy.
[0087] After the irradiation reaction is completed, the homogeneous solution is reversely precipitated in an aqueous solution, washed repeatedly for multiple times, soaked in deionized water for 24 hours, and then dried in a vacuum drying oven (80° C.) to constant weight.
[0088] (2) Preparation of impregnation solution:
[0089] A certain amount of modified polyethersulfone resin powder was weighed, added with DMF, and stirred for 30 minutes using a high-speed shear disperser to fully dissolve it to form a solution A with a solid content of 30%wt, wherein the weight average molecular weight of the polyethersulfone powder was 50,000.
[0090] A certain amount of polyurethane resin solution was weighed, DMF was added, and the mixture was dispersed by high-speed stirring in a stirrer for 30 minutes to form solution B, wherein the solid content was controlled at 30%wt. The 100% modulus of the polyurethane resin was 7Mpa.
[0091] A certain amount of polyacrylic acid was weighed and added into the first solvent DMF, and dispersed with high-speed stirring for 30 minutes to obtain a solution C with a solid content of 1% wt.
[0092] The three solutions A, B and C are mixed in a mass ratio of 90:10:15, stirred and degassed to form an impregnation solution, which is then left to stand for use. In the impregnation solution, the polyurethane resin accounts for 10% of the resin mass, the polyacrylic acid accounts for 0.5% of the resin mass, the content of the modified polyethersulfone resin in the impregnation solution is 23.5wt%, the content of the polyurethane resin in the impregnation solution is 2.6wt%, and the content of the pore-forming agent in the impregnation solution is 0.1wt%.
[0093] (3) Wet forming of polishing pad:
[0094] The non-woven fabric base is pre-treated in an oven at 100°C for 2 hours to remove moisture, and then the non-woven fabric base is immersed in the impregnation liquid, and the excess floating material on the surface is squeezed out by a pressure roller. The non-woven fabric base is immersed in the coagulation liquid to make the impregnation liquid coagulate on the non-woven fabric fibers. After washing with water, it is dried at 120°C for 2 hours to obtain a semi-finished polishing pad.
[0095] The coagulation liquid is an aqueous solution of N,N-dimethylformamide, and the concentration of N,N-dimethylformamide is 20wt%. The non-woven fabric is made of short fibers by needle punching process, and the fiber raw material is selected from polyester short fibers with a fiber fineness of 3 deniers. The thickness of the non-woven fabric is 2mm and the weight is 300g / m 2 .
[0096] (4) Polishing pad processing
[0097] Grind both sides of the semi-finished polishing pad with 180-grit sandpaper to control the thickness of the product to 1.3mm. Then stick double-sided tape on one side and make grooves on the other side. After completion, the polishing pad is finished.
[0098] Example 2
[0099] This embodiment provides a specific method for preparing a polishing pad. The preparation steps are basically the same as those in Embodiment 1, except that:
[0100] In step (2), the pore-forming agent is polyvinyl alcohol, and the three solutions A, B, and C are mixed in a mass ratio of 70:30:15. In the impregnation liquid, the polyurethane resin accounts for 30% of the resin mass, the polyvinyl alcohol accounts for 0.5% of the resin mass, the content of the modified polyether sulfone resin in the impregnation liquid is 18.3wt%, the content of the polyurethane resin in the impregnation liquid is 7.8wt%, and the content of the pore-forming agent in the impregnation liquid is 0.1wt%.
[0101] Example 3
[0102] This embodiment provides a specific method for preparing a polishing pad. The preparation steps are basically the same as those in Embodiment 1, except that:
[0103] In step (2), the molecular weight of the modified polyethersulfone resin particles is 40000, and the three solutions A, B, and C are mixed in a mass ratio of 80:20:25. In the impregnation solution, the polyurethane resin accounts for 20% of the resin mass, the polyacrylic acid accounts for 0.8% of the resin mass, the content of the modified polyethersulfone resin is 19.2%wt%, the content of the polyurethane resin in the impregnation solution is 4.8wt%, and the content of the pore-forming agent in the impregnation solution is 0.2wt%.
[0104] Example 4
[0105] This embodiment provides a specific method for preparing a polishing pad. The preparation steps are basically the same as those in Embodiment 1, except that:
[0106] In step (2), the molecular weight of the modified polyethersulfone resin particles is 40,000, the 100% modulus of the polyurethane resin is 15 MPa, the pore-forming agent is polyvinyl alcohol, and the three solutions A, B, and C are mixed in a mass ratio of 80:20:25. In the impregnation liquid, the polyurethane resin accounts for 20% of the mass of the resin, the polyvinyl alcohol accounts for 0.8% of the mass of the resin, the content of the modified polyethersulfone resin is 19.2wt%, the content of the polyurethane resin in the impregnation liquid is 4.8wt%, and the content of the pore-forming agent in the impregnation liquid is 0.2wt%.
[0107] Example 5
[0108] This embodiment provides a specific method for preparing a polishing pad. The preparation steps are basically the same as those in Embodiment 1, except that:
[0109] In step (2), the molecular weight of the modified polyethersulfone resin particles is 40000, the solid content of solutions A and B is 25%wt, and the three solutions A, B, and C are mixed in a mass ratio of 80:20:25. In the impregnation liquid, the polyurethane resin accounts for 20% of the resin mass, the polyacrylic acid accounts for 1% of the resin mass, the content of the modified polyethersulfone resin is 16wt%, the content of the polyurethane resin in the impregnation liquid is 4.0wt%, and the content of the pore-forming agent in the impregnation liquid is 0.1wt%.
[0110] Comparative Example 1
[0111] This comparative example is a comparative example of Example 3, except that:
[0112] In step (2), solutions B and C are mixed at a mass ratio of 100:25, the impregnating solution does not contain modified polyethersulfone resin, polyacrylic acid accounts for 0.8% of the resin mass, and the 100% modulus of the polyurethane resin is 30 MPa.
[0113] Comparative Example 2
[0114] This comparative example is a comparative example of Example 3, except that:
[0115] In step (2), the pore-forming agent is polyvinyl alcohol, and the two solutions A and C are mixed at a mass ratio of 100:25. The impregnation solution does not contain polyurethane resin, and polyacrylic acid accounts for 0.8% of the mass of the resin.
[0116] Comparative Example 3
[0117] This comparative example is a comparative example of Example 5, except that:
[0118] In step (2), the impregnation liquid does not contain a pore-forming agent, and the rest is the same as in Example 5, and the polyurethane resin accounts for 20% of the resin mass.
[0119] Comparative Example 4
[0120] This comparative example is a comparative example of Example 1, except that:
[0121] In step (2), the three solutions A, B and C are mixed in a mass ratio of 95:5:15. In the impregnation solution, the polyurethane resin accounts for 5% of the resin mass, and the polyacrylic acid accounts for 0.5% of the resin mass.
[0122] Comparative Example 5
[0123] This comparative example is a comparative example of Example 1, except that:
[0124] In step (2), the three solutions A, B and C are mixed in a mass ratio of 60:40:15. In the impregnation solution, the polyurethane resin accounts for 40% of the resin mass, and the polyacrylic acid accounts for 0.5% of the resin mass.
[0125] Comparative Example 6
[0126] This comparative example is a comparative example of Example 3, except that:
[0127] In step (2), the solid content of the prepared C solution is 0.12%. In the impregnation solution, the polyurethane resin accounts for 20% of the resin mass, and the polyacrylic acid accounts for 0.1% of the resin mass.
[0128] Comparative Example 7
[0129] This comparative example is a comparative example of Example 3, except that:
[0130] In step (2), the solid content of the prepared C solution is 1.8%. In the impregnation solution, the polyurethane resin accounts for 20% of the resin mass, and the polyacrylic acid accounts for 1.5% of the resin mass.
[0131] Comparative Example 8
[0132] This comparative example is a comparative example of Example 3, except that:
[0133] In step (2), the modified polyethersulfone is replaced by polyethersulfone, and the other conditions remain unchanged.
[0134] The molecular weight test of polyethersulfone resin and the molecular weight test and 100% modulus test of polyurethane resin are as follows:
[0135] Molecular weight test: The molecular weight was determined by gel permeation chromatography.
[0136] 100% Modulus Test Method:
[0137] 1) Preparation of polyurethane sheet: Attach the four sides of a PET plastic sheet flatly to a glass plate, pour the polyurethane resin solution on the PET plastic sheet, and use a scraper to evenly scrape the film on the flat and smooth PET plastic sheet, and try to avoid bubbles during scraping. The thickness of the film is 0.4 mm.
[0138] 3) Drying: Place in a 50°C oven and dry at a constant temperature for 20 minutes, then heat to 120°C, dry for 30 minutes, take out, and naturally cool to room temperature before tearing off the polyurethane sheet from the glass plate.
[0139] 4) Storage: Put into a ziplock bag and place in a constant temperature room at 25℃±2℃ for 4 hours before testing.
[0140] 5) Prepare the test strip (polyurethane sheet):
[0141] The sample strip to be tested is 20mm×120mm, and the long side direction is parallel to the scraping direction during film making when cutting. The middle part with high thickness uniformity is selected to avoid bubbles, concave and convex points, with no surface defects and neat incision edges. Five valid sample strips are taken each time.
[0142] Take the average thickness (mm) of the 5 points of the specimen to be tested using a thousandths thickness gauge.
[0143] 6) Tensile test of the specimen to be tested:
[0144] Turn on the tensile testing machine, the clamp distance of the tensile testing machine is 35mm, the stretching speed is 200mm / min, and the tensile load kgf when the stretching degree is 100% is obtained. The 100% tensile modulus is calculated according to the following formula:
[0145] 100% tensile modulus = tensile load kgf at 100% elongation / sample cross-sectional area (width × thickness of the sample to be tested) cm 2 .
[0146] The polishing pads prepared in Examples 1 to 5 and Comparative Examples 1 to 8 and the commercially available silicon carbide polishing pad suba800 (manufactured by DuPont) were subjected to hardness test, density test, compression ratio and compression elastic modulus test, air permeability test, and oxidation resistance test, respectively. The test results are shown in Table 1. The polishing pads of Example 3 and Comparative Examples 1 and 7 that were subjected to oxidation resistance test were as follows: Figures 7 to 9 shown.
[0147] The polishing pads prepared in Example 3, Comparative Examples 1 to 3, and Comparative Example 8 and the commercially available product suba800 were subjected to polishing rate tests and scratch tests, respectively. The test results are shown in Figures 1-2 and Tables 2-3.
[0148] The polishing pads prepared in Example 3 and Comparative Examples 6-7 were subjected to polishing rate test and scratch test respectively. The test results are shown in Figures 5-6 and Tables 2-3.
[0149] The polishing pads prepared in Example 1 and Comparative Examples 4-5 were subjected to polishing rate test and scratch test respectively. The test results are shown in Figures 3-4 and Tables 2-3.
[0150] After 20 hours of polishing test, the polishing pads of Example 3 and Comparative Examples 1 and 7 are as follows Figures 10-12 shown.
[0151] The test method is as follows:
[0152] 1. Hardness test: GB / T 2411-2008 test;
[0153] 2. Density test: GB / T 6343-2009 is used to measure the apparent core density. The size of the sample to be tested is 300mm×300mm×3.0mm;
[0154] 3. Compression ratio and compression elasticity test: Tested by Method A (constant pressure method) in GB / T 24442.1-2009 Determination of compression properties of textiles Part 1: Constant method;
[0155] 4. Air permeability test: Fabric air permeability tester equipment, model G571, setting parameters: test area 38cm 2 , test pressure 1000Pa.
[0156] 5. Oxidation resistance test:
[0157] Prepare an alkaline potassium permanganate solution (mass fraction 5.2% pH = 9), soak the polishing pad in the alkaline potassium permanganate solution for 24 hours, take out the polishing pad and put it in clean water for ultrasonic cleaning twice, each time for 10 minutes, then put it in 2.5% oxalic acid solution for ultrasonic cleaning for 10 minutes, and then clean water for ultrasonic cleaning for 10 minutes to obtain the sample to be tested. The wear resistance of the sample to be tested is measured by Taber abrasion tester, using H-18 ceramic grinding wheel with a load of 1.5kg weight for abrasion, and the loss mass is tested after rotating 500 times at a speed of 75rpm.
[0158] 6. Polishing rate test: A single-sided polishing machine with size 36B from Zhejiang Mingzheng was used to polish a 6-inch silicon carbide substrate and record the polishing rate; polishing machine table: 915mm, polishing liquid used was Bolinerun silicon carbide polishing liquid COPOL-233, polishing liquid flow rate was 400ml / min, polishing pressure: 238g / cm 3 , lower disc speed 40rpm.
[0159] 7. Scratch detection: The silicon carbide substrate for polishing rate test was subjected to scratch detection and observed with the naked eye under a strong light (Yamada Optics YP250). Bright lines longer than 2 cm were identified as scratches, and the number of scratches was recorded.
[0160] Table 1
[0161]
[0162] Table 2
[0163]
[0164]
[0165] Table 3
[0166]
[0167] From Table 1 we can see that:
[0168] The air permeability of Examples 1 to 5 of the present application is 100 m 2 / s or more, while in Comparative Example 3, since there is no pore-forming agent, the air permeability of the polishing pad prepared is as low as 2m 2 / s, indicating that the pore-forming agent can greatly improve the air permeability of the polishing pad;
[0169] The wear amount of Examples 1 to 5 of the present application is controlled within 100 mg. However, since Comparative Example 1 does not contain modified polyethersulfone resin, its wear amount reaches 623 mg after 500 rounds of grinding after soaking in potassium permanganate solution, indicating that modified polyethersulfone resin plays an important role in improving the oxidation resistance of the polishing pad.
[0170] from Figure 1It can be seen that:
[0171] The polishing rates of Comparative Example 1 and the commercial product suba800 decreased rapidly. This is because the polishing pad prepared in Comparative Example 1 and the commercial product suba800 have poor oxidation resistance. As the polishing time increases, the internal resin is severely corroded, affecting the overall physical properties. Therefore, the polishing rate decreases rapidly, and after 10 hours, the polishing pad is seriously damaged, so the test is stopped.
[0172] Since the polishing pad of Comparative Example 3 does not contain a pore-forming agent, it has few internal pores and poor ability to store polishing liquid. Therefore, the polishing rate is lower than that of Example 3 and Comparative Example 2.
[0173] The polishing rates of Example 3 and Comparative Example 2 are relatively stable within 20 hours, with almost no attenuation. Moreover, since the polishing pad of Comparative Example 2 does not contain polyurethane resin, its oxidation resistance is higher than that of Example 3. Therefore, the polishing rate of Comparative Example 2 is better than that of Example 3.
[0174] from Figure 2 It can be seen that:
[0175] The polishing pad of Comparative Example 2 has an average of more than 10 scratches. This is because the resin in the polishing pad is modified polyethersulfone resin, which has high hardness and poor elasticity. During polishing, the friction force with the surface of the SiC substrate is large, resulting in a large number of scratches.
[0176] The polishing pad of Comparative Example 3 has a large number of scratches. This is because the internal pores are small, resulting in the accumulation of abrasives, which easily scratches the SiC substrate during polishing.
[0177] from Figure 3 It can be seen that the removal rate and stability of Example 1 and Comparative Example 4 are good, the polishing rate of Comparative Example 5 is slightly lower, and with the extension of the use time, the attenuation amplitude is also relatively large, and finally after 16 hours it is lower than 1.5 μm / h. This is due to the relatively small content of modified polyethersulfone and insufficient chemical oxidation resistance.
[0178] from Figure 4 It can be seen that the number of scratches in Example 1 and Comparative Example 5 is controlled within the range of no more than 3, while that in Comparative Example 4 exceeds the standard, indicating that too much modified polyethersulfone component will increase the hardness and deteriorate the elasticity of the final product, resulting in too many scratches during polishing.
[0179] from Figure 5It can be seen that the removal rate and stability of Example 3 are both good, and the rate stability of Comparative Example 6 is good, but the average removal rate is lower than that of Example 3. This is because the internal pore structure of Comparative Example 6 is relatively small, which is not conducive to the circulation of the polishing liquid. The initial removal rate of Comparative Example 7 is good, but it decays significantly in the later period, and is lower than 1.5 μm / h after 18 hours. This is because too many pore structures will accelerate the corrosion of potassium permanganate in the polishing liquid to the inside of the polishing pad, thereby causing the removal rate to decrease.
[0180] from Figure 6 It can be seen that the number of scratches in Example 3 and Comparative Example 7 is within 3, while that in Comparative Example 6 is obviously over the limit. This is because the less porous structure makes it easier for the abrasive particles in the polishing liquid and the impurities removed by polishing to cause blockage inside the polishing pad, causing scratches during polishing.
[0181] from Figures 7 to 9 It can be seen that the polishing pad of Example 3 has basically no fuzz on its surface, the polishing pad of Comparative Example 1 has a lot of fiber fluff on its surface because there is no modified polyethersulfone resin in the polishing pad, and the polishing pad of Comparative Example 7 has some fuzz on its surface because the content of modified polyethersulfone resin is relatively low.
[0182] from Figures 10-12 It can be seen that the polishing pad of Example 3 has basically no fuzz on its surface, the polishing pad of Comparative Example 1 has a lot of fiber fluff on its surface because there is no modified polyethersulfone resin in the polishing pad, and the polishing pad of Comparative Example 7 has some fuzz on its surface because the content of modified polyethersulfone resin is relatively low.
[0183] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A polishing pad, characterized in that: The invention comprises a base material, wherein the base material is impregnated with a resin material, wherein the raw material components of the resin material comprise a resin and a pore-forming agent; the resin comprises a modified polyethersulfone resin and a polyurethane resin; the polyurethane resin accounts for 10% to 30% of the mass of the resin; the modified polyethersulfone resin accounts for 70% to 90% of the mass of the resin; the pore-forming agent accounts for 0.3 to 1% of the mass of the resin; the modified polyethersulfone resin is obtained by a grafting reaction of acrylic acid and polyethersulfone; the mass ratio of the polyethersulfone to the acrylic acid is 10:(0.1 to 1); the pore-forming agent is selected from polyacrylic acid and / or polyvinyl alcohol; the weight average molecular weight of the modified polyethersulfone resin is 10,000 to 70,000; and the 100% modulus of the polyurethane resin is 1 to 15 MPa.
2. The polishing pad according to claim 1, characterized in that The raw material components further include a first solvent, which is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
3. The polishing pad according to claim 1, characterized in that The base material is selected from one of fabric, non-woven fabric or woven fabric; and / or the fiber raw material of the base material has a fiber fineness of 2.6 to 3 deniers.
4. The polishing pad according to claim 1, characterized in that The polishing pad includes one or more of the following features: a) Density is 0.4~0.5g / cm 3 ; b) Shore A hardness is 80~91HA; c) Compression rate is 2.0~4.0%; d) Compression elasticity is 60~75%; e) Air permeability is not less than 100m 2 / S; f) After being immersed in an alkaline potassium permanganate solution with a concentration of 4.5-5.5% and a pH of 8.5-9.5, the surface was abraded with an H-18 ceramic grinding wheel with a load of 1-2 kg and rotated 500-600 times at a speed of 60-75 rpm, and the wear loss was not higher than 100 mg.
5. A method for preparing a polishing pad according to any one of claims 1 to 4, characterized in that: The steps include: 1) mixing the raw material components to form a homogeneous impregnation solution; 2) The base material is immersed in the immersion liquid, and then placed in a coagulation liquid for coagulation to obtain the polishing pad.
6. The preparation method according to claim 5, characterized in that: In the impregnation solution, the content of the modified polyethersulfone resin is 15-25wt%; And / or, in the impregnation liquid, the content of the polyurethane resin is 2-10wt%; and / or, in the impregnation solution, the content of the pore-forming agent is 0.1-0.2wt%; And / or, the impregnation is followed by a rolling process; and / or, the coagulation liquid is an aqueous solution of N,N-dimethylformamide; and / or, after the coagulation treatment, one or more treatments selected from washing, drying, grinding, and grooving are performed; And / or, the thickness of the base material is 1.8-2.2 mm, and the weight is 270-330 g / cm 2 .
7. The preparation method according to claim 6, characterized in that: In the coagulation liquid, the content of N,N-dimethylformamide is 15-25 wt %; and / or the rotation speed of the rubber roller is 1-5 r / min, and the roller pressure is 0.1-1 MPa.
8. Use of the polishing pad according to any one of claims 1 to 4 as a polishing pad for polishing a silicon carbide substrate in chemical mechanical polishing.
Citation Information
Patent Citations
Polishing pad and process for production of polishing pad
CN101600540B
Rigid sheet and process for manufacturing rigid sheet
CN105008614A
Polishing pad and method of manufacturing polishing pad
JP2012101333A
Glass polishing pad and preparation method thereof
CN111941271A
Composite CMP liner constructions using additive manufacturing processes
CN113579992A